Greenhouse Gas Emissions after Application of Landfilled Paper Mill Sludge for Land Reclamation of a Nonacidic Mine Tailings Site. Issue 5 (1st September 2017) - Faubert, Patrick; Durocher, Simon; Bertrand, Normand; Ouimet, Rock; Rochette, Philippe; Tremblay, Pascal; Boucher, Jean‐François; Villeneuve, Claude
Abstract : Large areas of mine tailings are reclaimed by applying organic amendments such as paper mill sludge (PMS). Although mining industries can use PMS freshly generated by paper mills, operational constraints on paper industries make temporary landfilling of this material an unavoidable alternative for the paper industries, creating the most prominent PMS source for mining industries. This study aimed to quantify soil greenhouse gas (GHG) emissions (N2 O, CO2, and CH4 ) after application of landfilled PMS (LPMS; i.e., excavated from a landfill site at a paper mill) and LPMS combined with a seeding treatment of white clover ( Trifolium repens L.) on nonacidic mine tailings site prior to reforestation. Soil N2 O, CO2, and CH4 fluxes were measured after applications of 50 and 100 Mg dry LPMS ha −1 during two consecutive snow‐free seasons on two adjacent sites; LPMS was applied once in the first season. The LPMS application increased N2 O emissions (7.6 to 34.7 kg N2 O‐N ha −1, comprising 1.04 to 2.43% of applied N) compared with the unamended control during the first season; these emissions were negligible during the second season. The LPMS application increased CO2 emissions (∼5800 to 11, 400 kg CO2 –C ha −1, comprising 7 to 27% of applied C) compared with the unamended control on both sites and in both seasons. Fluxes of CH4 were negligible. White clover combined with LPMS treatments did not affect soil GHG emissions. These new GHG emission factors should be integrated into life‐cycle analyses to evaluate the C footprint of potential symbioses between the mining and paper industries. Future research should focus on the effect of PMS applications on soil GHG emissions from a variety of mine tailings under various management practices and climatic conditions to plan responsible and sustainable land reclamation. Core Ideas: Applied PMS for mine tailings reclamation affected GHG emissions. PMS application increased N2 O and CO2 emissions, whereas CH4 fluxes were negligible. White clover combined with PMS treatments did not affect soil GHG emissions. Mine and paper industries can integrate these GHG emissions into industrial symbioses.